1998
DOI: 10.1097/00002030-199810000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression and survival in HIV-1-infected Africans in London

Abstract: Differences in progression to AIDS and death and CD4+ lymphocyte decline between HIV-1-infected Africans and non-Africans in London could not be attributed to ethnicity or different viral subtypes. Age and the clinical and immunological stage at presentation, or AIDS, were the major determinants of outcome. Compared with other diagnoses, tuberculosis as the initial ADC was associated with increased survival. Lack of access to health care and exposure to environmental pathogens are the most likely causes of red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(24 citation statements)
references
References 32 publications
1
22
1
Order By: Relevance
“…The majority of heterosexually acquired HIV infections in Europe are now in immigrants from high prevalence countries, who, like persons from ethnic minorities, present late to health services [116][117][118]. For example, in the UK, black Africans with HIV/AIDS, were more likely to present to outpatient clinics at an advanced stage of disease, but once diagnosed with HIV, their use of services was similar to that of the PLWHA who were not of black African origin [119][120][121][122][123][124][125].…”
Section: Services For the Socio-economically Disadvantaged Groupsmentioning
confidence: 99%
“…The majority of heterosexually acquired HIV infections in Europe are now in immigrants from high prevalence countries, who, like persons from ethnic minorities, present late to health services [116][117][118]. For example, in the UK, black Africans with HIV/AIDS, were more likely to present to outpatient clinics at an advanced stage of disease, but once diagnosed with HIV, their use of services was similar to that of the PLWHA who were not of black African origin [119][120][121][122][123][124][125].…”
Section: Services For the Socio-economically Disadvantaged Groupsmentioning
confidence: 99%
“…These data are encouraging, because once the migrants are actually treated by the national health services in Europe, no differences can be observed in the intake of HAART, in progression to AIDS and in survival compared to native patients. 7,[14][15][16][17][18] The most commonly used regimen (44.8%) was composed of two nucleoside analogues and a non-nucleoside inhibitor that might reflect the clinicians apprehension about the use of more complex regimens; a once-daily regimen, however, was chosen only in a low percentage of cases (3%).…”
Section: Hiv-infected Immigrants and Access To Haart 603mentioning
confidence: 99%
“…Once started on HAART, immunological and virological responses are equivalent in African and white UK patients (Frater et al ., 2002) and the response is at least as good in women as in men (Moore et al ., 2002). However, African patients appear to present to services at a more advanced stage of HIV disease compared to whites (Barry et al ., 2002;Del Amo et al ., 1998;Saul et al ., 2000). Several studies have shown a low self-perceived risk of HIV in African populations in the UK (Erwin et al ., 2002;Fenton et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%